Pedagogical blog: university lecturers' perception and application - Tan, Bee Hoon; Abdullah, Mardziah Hayati; Yong, Mei Fung (Penerbit Universiti Teknikal Malaysia Melaka, 2012)
Recent studies have found the values of weblog in extending teaching and learning beyond the space and time of a classroom. The pedagogical application of blog have resulted in various benefits in instructional processess. However, not much research has been conducted in this area locally. In view of the research gap, a survey study was undertaken to mainly investigate the extent of blog application for pedagogical purposes at the tertiary level. The results of the study reveal that 45% of a total of 207 lecturers surveyed admitted using blog in their instructional processes. Various reasons were given to the non-use of blog. For those who applied blog, the purposes include communication, discussion of course content and assignment, activity log, posting assignments for assessment, reflective thinking and writing practice. Other important findings and implications were also drawn from the study.